Are Owls and Larks Different When it Comes to Aggression? Genetics, Neurobiology, and Behavior - Deibel, Scott H.; McDonald, Robert J.; Kolla, Nathan J. (Frontiers in Behavioral Neuroscience, 2020)
This review focuses on the contribution of circadian rhythms to aggression with a multifaceted approach incorporating genetics, neural networks, and behavior. We explore the hypothesis that chronic circadian misalignment is contributing to increased aggression. Genes involved in both circadian rhythms and aggression are discussed as a possible mechanism for increased aggression that might be elicited by circadian misalignment. We then discuss the neural networks underlying aggression and how dysregulation in the interaction of these networks evoked by circadian rhythm misalignment could contribute to aggression. The last section of this review will present recent human correlational data demonstrating the association between chronotype and/or circadian misalignment with aggression. With circadian rhythms and aggression being a burgeoning area of study, we hope that this review initiates more interest in this promising and topical area.